Comparing "exclusion" and "neutralization" for computing core inflation: Results for the Philippines - Dumagan, Jesus C. (Animo Repository, 2022)
Core inflation removes from headline inflation (i.e., overall CPI inflation) volatile prices. One way for removal is “exclusion” of selected commodities by setting their weights to zero, which is practiced in the Philippines—and in Brazil, Israel, Korea, Poland, and the United States, to name a few—where “food” and “energy” items are excluded. Using Philippine Statistics Authority CPI data (January 2012–July 2021) and procedures, this paper shows that core inflation by exclusion is misleading because it could be higher than headline inflation when the excluded items have positive inflation contributions. To avoid this misleading result, this paper proposes “neutralization” of the excluded commodities by keeping them in the CPI basket but making their CPIs constant, thus, neutralizing them because, in this case, they cannot contribute to inflation. Neutralization yields the logical result that core inflation is lower (higher) than headline inflation if the neutralized commodities have positive (negative) total inflation contributions. Moreover, neutralizing commodities with inflation contributions that are not statistically significantly different from zero yields core inflation with statistically the same mean but lower variance than headline inflation. A sufficient but not necessary condition to lower variance is derived that in practice is very rarely violated. Thus, neutralization permits more precise inflation forecasts for the purposes of monetary policy consistent with the overall or headline price trend of the economy.